JENIS-JENIS KEGIATAN ADMINISTRASI KESISWAAN BERDASARKAN KURIKULUM - Mahdayeni Mahdayeni (P3M IAI Nusantara Batang Hari, 2016)
Educational administration consists of two main ideas , namely administration and education . Administration comes from the Latin , which consists of